Computational Thinking in Solving Arithmetic Sequences Problems for Slow Learners: Single Subject Research - Zulfa, Faradina Nilam; Andriyani, Andriyani (Universitas Islam Negeri Sunan Kudus, 2023)
The importance of mathematical problem-solving skill shows that it is very important to develop it as an integrated part of learning mathematics process. However, some prior research results show that students' problem-solving skill is still relatively low, especially for slow learners. The students as slow learners require external stimulation or encouragement to help them to simplify complex problems into simple one. One of stimulations or encouragements is a computational thinking technique. The computational thinking technique in this research includes four principles namely decomposition, abstraction, pattern recognition, and algorithms. This research aims to determine the use of computational thinking for slow learners in solving problems related to arithmetic sequences. The method used in this research is single-subject research having two students as research subjects in one group. The data collection techniques include observation and students’ test results and the data analysis techniques used are within-conditions analysis and between-conditions analysis with an A-B research design. The A-B research design is one of designs in Single Subject Research (SSR) method, with A as the baseline phase and B as the intervention phase. The results show that in the baseline phase, the students receive a final score in the range of 20 to 30 and in the intervention phase, after being given a computational thinking technique as a treatment, students' final scores increase to the range of 50 to 60. This shows that there is positive effect using computational thinking technique for slow learners in solving arithmetic sequences problems. Pentingnya peran pemecahan masalah matematika menunjukkan perlunya mengembangkan kemampuan tersebut sebagai bagian integral dari pembelajaran matematika. Namun, beberapa hasil penelitian terdahulu menunjukkan bahwa kemampuan pemecahan masalah siswa masih terbilang rendah, terkhusus siswa lamban belajar. Keterbatasan siswa lamban belajar memerlukan rangsangan atau dorongan dari luar untuk membantu siswa lamban belajar menyederhanakan permasalahan yang kompleks menjadi beberapa masalah sederhana, seperti pendekatan berpikir komputasional. Pendekatan berpikir komputasi dalam penelitian ini mencakup empat prinsip, yakni dekomposisi, abstraksi, pengenalan pola dan algoritma. Penelitian ini bertujuan untuk mengetahui peran berpikir komputasi untuk siswa lamban belajar dalam menyelesaikan permasalahan terkait barisan aritmetika. Penelitian ini menggunakan metode Single Subject Research dimana subyek dalam penelitian ini adalah dua siswa dalam satu kelompok. Teknik pengumpulan data meliputi observasi dan hasil tes siswa. Teknik analisis data menggunakan analisis dalam kondisi dan analisis antar kondisi dengan desain penelitian A-B. Desain penelitian A-B merupakan salah satu desain dari Single Subject Research (SSR) dengan A sebagai fase baseline dan B sebagai fase intervensi. Hasil penelitian menunjukkan bahwa pada fase baseline, subjek mendapatkan skor akhir pada kisaran 20 hingga 30, dan pada fase intervensi, setelah diberikan perlakuan berupa pendekatan berpikir komputasi, skor akhir siswa meningkat menjadi dalam rentang 50 sampai 60. Hal ini menunjukkan bahwa penggunaan pendekatan berpikir komputasi berpengaruh positif terhadap pemecahan masalah siswa lamban belajar terkait barisan aritmatika.